Penatalaksanaan Gout Arthritis dan Hipertensi Grade I pada Wanita Lansia Obesitas melalui Pendekatan Dokter Keluarga - Intan Hardianti; Diana Mayasari (CV. Jasa Sukses Abadi, 2020)
Gout or commonly known as gout arthritis is a disease caused by the accumulation of monosodium uric crystals in the body. Gout is estimated to occur in 840 people out of 100,000 people. Hypertension is a state of systolic blood pressure of more than 140 mmHg and diastolic of more than 90 mmHg. Based on blood pressure measurements, the prevalence of hypertension in the population aged 18 years and above in 2013 in Indonesia is 25.8%. The use of evidence-based medicine of family doctor services is done by identifying risk factors, identifying clinical problems, and patient management based on the framework of solving patient problems through a patient-centered and family approach. This is a case report study. Assessment is done based on initial diagnosis, process, and end of study qualitative and quantitatively. The patient was a 63-year-old female, a housewife. Patients were diagnosed with Class I Gout Arthritis and Hypertension, and Class II Obesity. Patients and families have less knowledge about the disease and unhealthy lifestyles. This is a risk factor for disease complications in patients. Gout Arthritis and hypertension with less knowledge about risk factors, adherence to routine drug use, and compliance with periodic control to the doctor can cause acute and advanced complications. Complications can be prevented by the family doctor approach.